Gambaran Strategi Pemasaran Produk Asuransi Kesehatan Unit Link di PT. Prudential Life Assurance Cabang Mojokerto - Maudy Mei Diana; Budi Susatia; Bernadus Rudy Sunindya (Kementerian Kesehatan Poltekkes Malang, 2024)
Marketing strategy is a plan to be followed by marketing managers. This action plan is based on situational analysis and company goals and is a way to achieve those objectives. The aim of this study is to understand the marketing strategy for unit-linked health insurance products, determine the increase in the number of participants, and identify obstacles in marketing these products. This study uses a qualitative case study method. Data collection techniques include interviews, which are then presented in text and supported by graphs or diagrams. The research results indicate that the sales of unit-linked health insurance products at PT. Prudential Life Assurance Mojokerto Branch have increased each year. The researcher hopes that future studies will further develop research objectives and expand literature reviews on the research focus